Does Prenatal Stress Management Enhance Maternal And Fetal Outcomes? - Ghada Mohammad Abu Shosha (European Scientific Journal, ESJ, 2016)
Background: Antenatal period is a time of rapid change during which fetal organs are vulnerable to various stressors. Studies have suggested that psychosocial stressors during pregnancy could adversely influence physical and behavioral outcomes of the infant. Aim: This paper aimed to discusses the importance of antenatal stress assessment and management on both mothers' and infants' health status. Method: This review aggregated evidence from various studies that examined the impact of maternal stress management and its outcomes on pregnant women and their infants. Results: Maternal stress is generally associated with unpleasant fetal outcomes. The use of stress reduction techniques was approved to reduce psychological stress in pregnant women. Conclusion: Ongoing assessment of antenatal stress using a standardized process promotes proper stress handling strategy.